Six‐Membered Cyclic Nitroso Acetals: Synthesis and Studies of the Nitrogen Inversion Process of N‐Silyloxy‐3, 6‐dihydro‐2H‐1, 2‐oxazines. Issue 33 (25th October 2016) - Shved, Alexander S.; Tabolin, Andrey A.; Novikov, Roman A.; Nelyubina, Yulia V.; Timofeev, Vladimir P.; Ioffe, Sema L.
Abstract : Silyl nitronates undergo rhodium‐catalyzed formal [3+3]‐cycloaddition with enol diazoacetates to form N ‐silyloxy‐3, 6‐dihydro‐2 H ‐1, 2‐oxazines. The scope of the reaction and the extent of the major side process were evaluated. A mechanistic scheme was proposed. The nitrogen inversion barrier in the obtained nitroso acetals was estimated based on both quantum calculations and kinetic measurements. Abstract : The reaction of silyl nitronates and enol diazoacetates affords N ‐silyloxy‐3, 6‐dihydro‐2 H ‐1, 2‐oxazines as a new type of nitroso acetal. The scope of the reaction was established. Quantum chemical calculations and kinetic data allowed the nitrogen inversion barrier in the target nitroso acetals to be determined.